Cost-effectiveness and public health benefit of secondary cardiovascular disease prevention from improved adherence using a polypill in the UK. Issue 5 (9th May 2015) - Becerra, Virginia; Gracia, Alfredo; Desai, Kamal; Abogunrin, Seye; Brand, Sarah; Chapman, Ruth; García Alonso, Fernando; Fuster, Valentín; Sanz, Ginés
Abstract : Objective: To evaluate the public health and economic benefits of adherence to a fixed-dose combination polypill for the secondary prevention of cardiovascular (CV) events in adults with a history of myocardial infarction (MI) in the UK. Design: Markov-model-based cost-effectiveness analysis, informed by systematic reviews, which identified efficacy, utilities and adherence data inputs. Setting: General practice in the UK. Participants: Patients with a mean age of 64.7 years, most of whom are men with a recent or non-recent diagnosis of MI and for whom secondary preventive medication is indicated and well tolerated. Intervention: Fixed-dose combination polypill (100 mg aspirin, 20 mg atorvastatin and 2.5, 5, or 10 mg ramipril) compared with multiple monotherapy. Primary and secondary outcome measures: CV events prevented per 1000 patients; cost per life-year gained; and cost per quality-adjusted life-year (QALY) gained. Results: The model estimates that for each 10% increase in adherence, an additional 6.7% fatal and non-fatal CV events can be prevented. In the base case, over 10 years, the polypill would improve adherence by ∼20% and thereby prevent 47 of 323 (15%) fatal and non-fatal CV events per 1000 patients compared with multiple monotherapy, with an incremental cost-effectiveness ratio (ICER) of £8200 per QALY gained. Probabilistic sensitivity analyses for the base-case assumptions showed an 81.5% chance of the polypill being cost-effective at a willingness-to-pay threshold of £20 000 per QALY gained compared with multiple monotherapy. In scenario analyses that varied structural assumptions, ICERs ranged between cost saving and £21 430 per QALY gained. Conclusions: Assuming that some 450 000 adults are at risk of MI, a 10 percentage point uptake of the polypill could prevent 3260 CV events and 590 CV deaths over a decade.The polypill appears to be a cost-effective strategy to prevent fatal and non-fatal CV events in the UK.